An introduction to information theory [ - Benavides, Hamza (New York : Learning Press, 2014)
This book provides an introductory approach to Information Theory
1. Introduction to information theory -- 2. Entropy -- 3. Noisy-channel coding theorem and mutual information -- 4. Quantities of information and coding theory -- 5. Channel capacity and binary symmetric channel -- 6. kullback-leibler divergence -- 7. Rate-distortion theory and algorithmic information theory -- 8. Inequalities in information theory and information flow -- 9. Fisher information and turbo code
Keywords: Information theory